2021
DOI: 10.1177/1049909121991807
|View full text |Cite
|
Sign up to set email alerts
|

Advance Care Planning—Complex and Working: Longitudinal Trajectory of Congruence in End-of-Life Treatment Preferences: An RCT

Abstract: Context: The effect of advance care planning (ACP) interventions on the trajectory of end-of-life treatment preference congruence between patients and surrogate decision-makers is unstudied. Objective: To identify unobserved distinctive patterns of congruence trajectories and examine how the typology of outcome development differed between ACP and controls. Methods: Multisite, assessor-blinded, intent-to-treat, randomized clinical trial enrolled participants between October 2013 to March 2017 from 5 hospital-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 50 publications
(41 reference statements)
1
16
0
2
Order By: Relevance
“…This study has some strengths. The findings confirm the results of 2 other trials of the FACE model, 25 , 26 using a rigorous trial design, 61 vigilant blinding of assessors, and high participant retention across a 2-year period, even though the studies were conducted in different patient groups and with different interventionists. This replication of findings provides confidence in the interpretation that the FACE-TC intervention can support long-term family knowledge of their adolescent’s end-of-life treatment preferences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study has some strengths. The findings confirm the results of 2 other trials of the FACE model, 25 , 26 using a rigorous trial design, 61 vigilant blinding of assessors, and high participant retention across a 2-year period, even though the studies were conducted in different patient groups and with different interventionists. This replication of findings provides confidence in the interpretation that the FACE-TC intervention can support long-term family knowledge of their adolescent’s end-of-life treatment preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Choices for each situation were as follows: to continue all treatments so I could live as long as possible (staying alive is most important to me no matter what), to stop all efforts to keep me alive (my definition of living well is more important than length of life), or unsure. The Statement of Treatment Preferences method has been used in multiple adolescent 25 , 28 , 30 and adult studies, 26 , 39 increasing its replicability.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a meta-analysis of RCTs (ACP vs usual care/attention-control intervention)7 8 10 12 16–25 assessing caregiver–patient congruence in EOL care preferences using Stata 17. We excluded one study that reported caregiver–patient congruence in EOL care preferences within latent classes 26. For studies reporting the outcome at multiple time points or hypothetical situations, we included results closest to the intervention and for situations where survival probability was deemed to be the lowest, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In RCTs across a wide range of populations from adolescent cancer, adult HIV, heart failure, and dementia patient, both interventions demonstrated efficacy in improved dyadic understanding and concordance of preferences, confidence in decision making, anxiety and depression among caregivers, and decisional conflict. [20][21][22][23][24][25][26][27] More recent dyadic ACP models primarily focused on the emotional and collaborative aspects of shared decisions by reducing emotional reactivity with mindfulness stress-reduction techniques; promoting improved consensus by having dyads complete advanced directives separately, then together; and emphasizing collaborative coping. [28][29][30][31] While these more recent models demonstrated preliminary efficacy in reducing decisional conflict, improving preference concordance, and lowering distress over time, they are largely limited by smaller sample sizes and the lack of a control group.…”
Section: Advanced Care Planning For Chronically Ill Adults and Their Caregivers (Presented By Djin Tay)mentioning
confidence: 99%